Molecular Imaging of Pancreatic Islet Transplantation - Liu, Y.; Song, B.; Ran, X.; Jiang, Q.; Hu, J.; Vance Chiang, S. M. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Islet replacement therapy, pancreatic islet transplantation, is considered as a potential option for curing T1DM. However, the significant loss of implanted islets after islet transplantation prevents it from becoming a mainstream treatment modality. Due to the lack of reliable noninvasive real-time imaging techniques to track the survival of the islets, it is impossible to discover the specific causes for the loss of implanted islets, not to mention taking interventions in the early stage. Current achievements in molecular imaging has provided with several promising techniques, including optical imaging, PET and MRI, for noninvasive visualization, quantification and functional evaluation of transplanted islets in experimental conditions. Optical imaging seems to be the most convenient and cost-efficient modality, but the limited penetration distance hinders its application in large animal and human studies. PET combined with target-specific tracers is characterized by high specificity and sensitivity for detection of islet grafts, but observation time is rather short (i.e., several hours). MRI stands out for its long-term visualization of transplanted islet grafts with the aid of contrast agents. However, quantification of islets remains a problem to be solved. A novel technique, microencapsulation, provides a new perspective in multimodal imaging by optimizing the strengths of several modalities together. Although the application of molecular imaging in clinical settings is still limited, significant success and valuable information is achieved in the basic and clinical trials. However, islet transplantation still remains an experimental procedure, with ongoing researches focusing on islets availability, appropriate sites for implantation, new methods using biomaterials (e.g. microencapsulation), immune modulation and more.
Keywords: diabetes mellitus; molecular imaging; pancreatic islet transplantation; contrast agent; islet labeling